2022
DOI: 10.1590/1414-431x2022e11819
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis indicators of type-2 diabetic COVID-19 patients

Abstract: Diabetes is associated with a worse prognosis and a high risk of morbidity and mortality in COVID-19 patients. We aimed to evaluate the main factors involved in the poor prognosis in diabetic patients. A total of 984 patients diagnosed with COVID-19 admitted to the hospital were included in this study. Patients were first divided into type-2 diabetic (DM+) and non-diabetic (DM–) groups. The participants were analyzed based on the National Early Warning Score (NEWS) and on the Quick-Sequential Organ Failure Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…In the present study, a higher peak value of leucocytes and neutrophils was associated with NOD. These findings were consistent with prior literature, showing that in coronavirus infection, NOD patients developed higher leukocytosis with neutrophilia than patients without DM [ 8 ]. This could be a marker for degradation of the clinical condition, with a high risk of a poor outcome, as shown in a meta-analysis with a total of 3377 COVID-19 patients [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, a higher peak value of leucocytes and neutrophils was associated with NOD. These findings were consistent with prior literature, showing that in coronavirus infection, NOD patients developed higher leukocytosis with neutrophilia than patients without DM [ 8 ]. This could be a marker for degradation of the clinical condition, with a high risk of a poor outcome, as shown in a meta-analysis with a total of 3377 COVID-19 patients [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…A high incidence of NOD in patients with SARS-CoV-2 infection was also previously reported. In a retrospective study reporting data from 453 patients admitted between January and March 2020 in Wuhan, China, Li et al [ 8 ] reported that 21.0% of COVID-19 patients without a previous diagnosis of DM had an FPG of 7.0 mmol/L or more and/or HbA1c of 6.5% or more. In another study enrolling 184 patients admitted for COVID-19 infection in Livingston, New Jersey between March and May 2020, Smith et al [ 21 ] reported that 15.8% of patients developed type 2 DM during the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with preexisting DM2 also presented worse prognosis in SARS-CoV infection ( Booth, 2003 ; Yang et al, 2006 ; Gorjão et al, 2022 ). Epidemiological studies also indicated that DM2 is the primary comorbidity associated with severe or lethal MERS-CoV infections ( Al-Qahtani et al, 2018 ).…”
Section: Metabolic Changes In Obesity Type 2 Diabetes and The Immune ...mentioning
confidence: 99%